Local culture in the context of international tourism : Japanese tourists' perceptions of the culture of Saariselkä and the views of Japanese travel agents - Aoyagi, Takumi (2012)
In tourism, cultures are often used as resources to attract tourists. This is because tourism is generated by difference. So that the culture of a tourist destination can be consumed by tourists the culture needs to go through commodification, a process through which part of the culture turns into a product or a service. Knowing how a culture is used for tourism practice is important from the viewpoint of the cultural sustainability of tourism.